Estudio económico para mejorar los costos de distribución del pollo faenado de la cadena de carnisariatos del portal en la ciudad de Guayaquil - Vargas Zapata, Denisse Stephanie (2018)
The optimization of costs in the chicken slaughter distribution chain for the Del portal carnisariatos company presents important challenges related to the characteristics of the products and production. The administration of the distribution chain offers important opportunities in terms of lower costs and new market perspectives; therefore, the response of the distribution chain for a specific poultry product is affected by the commercial and regulatory environment in which it operates, which generates a direct economic impact for the market and the company. This document studied the chicken slaughter distribution chain for the aforementioned organization, in which the influence of the productive environment on the structure of the industry and the adoption of commercial logistics were examined; with particular emphasis on processing and additional execution levels that establish their costs for distribution………….